Nutritional composition and sensory properties of snack bars made from sago worm paste (Rhynchophorus ferrugineus) as an alternative food - Canti Meda; Muliawan Shinta (BIO Web of Conferences)
Sago worms are a sustainable and nutritious food ingredient that requires further development to increase its wider utilization. This study aimed to develop snack bars made from sago worm paste and evaluate their proximate and sensory properties. The research stages included the preparation of sago worm paste and snack bars, followed by proximate and sensory analysis of the snack bars. Four formulas were used for the ratio of sago worm paste to wheat flour: 0:100 (F0), 25:75 (F1), 50:50 (F2), and 75:25 (F3). The ash, protein, lipid content, and total energy of the sago worm paste snack bars increased, while the acceptance scores for taste and aftertaste decreased. All snack bars were evaluated in accordance with the United States Department of Agriculture (USDA) standards. Additionally, the panellists accepted all snack bar treatments based on color, aroma, taste, aftertaste, texture, and overall acceptance. Formula F2 was found to be the best based on its nutritional composition and sensory properties.